Penerapan Eisenhower Matrix untuk Meningkatkan Manajemen Waktu Kerja pada Peserta Magang di Divisi Human Capital PT X - Dinda Cantika Putri; Noer Suci Endah Puspitaningrum (Indonesian Journal Publisher, 2025)
This study aims to determine the effectiveness of the Eisenhower Matrix in improving work time management among interns. This study used a one-group pretest and posttest design on six interns in the Human Capital Division. The intervention was provided through training led by professional psychologists who understood the use of the Eisenhower Matrix method, which is useful as a tool in prioritizing tasks based on their level of importance and urgency. Data were collected through measuring work time management before (pretest) and after (posttest) the intervention, after which it was analyzed using a paired sample t-test. The results showed an increase in the average time management score in the pretest from 75.17 to 105.83 in the posttest. The statistical test results showed a significant value of p 0.001 < 0.05, indicating a significant difference between work time management before and after the intervention. Thus, the application of the Eisenhower Matrix is ​​effective in helping interns determine work priorities, improve skills in completing tasks, and optimize work time effectively and systematically.